(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2022)
In the sources of classical Roman Law the term aes alienum is found to explain debts, especially debts deriving from a contract of loan. When Ulpianus in D. 50.16.213.1 Ulp. 1 reg. determines aes alienum as “money that we owe”, the jurist could try to explain an elder expression whose original meaning was not understood anymore in his times. From the pespective of property law, the interpretation of aes alienum as “foreign money”, aes suum as “own money” seems to be wrong. Therfore it has been discussed, if aes alienum could derive from an early stage of Roman law and originally has been understood in the meaning of th word. This could be compared to te so called “principle of surrogation” which is well known from ancient Greek Law. The following article tries to follow the traces of this principle in Greek and early Roman law.